Construction of windcatcher and necessity of enhancing the traditional windcatcher - Gorginpour A.; Jazayeri E. (Инженерно-строительный журнал, 2011)
In the past without modern facilities and modern equipment for cooling and heating, the architect was obliged to use economical engineering systems that rely on natural energy. This article evaluates one of such economical systems: the windcatcher used in traditional house of Iran. Nowadays the global warming is one of the most concern in the world and the necessity of using the sustainable systems could be a good solution for having a comfort zone with a suitable relative humidity and temperature with lowest fossil fuel consumption. This research has gathered the information about traditional windcatcher and its modern modifications. The advantages and disadvantages of different windcatcher shapes are analyzed. The methods for enhancing its construction are suggested.